Strategi Bank BRI Dalam Menjaga Likuiditas di Masa Pandemi COVID-19 - Lupita, Veronica; Maryana, Maryana; Lestari, Widia Ayuning (Jurnal Kompetitif Bisnis, 2020)
With the covid-19 pandemic still ongoing in Indonesia, liquidity problems are a challenge for the banking industry today. This article aims to discuss how the strategies used by BRI in maintaining liquidity in the midst of the covid-19 pandemic. BRI's LCR itself is still at 230%, above the minimum rate set by the OJK. This is inseparable from the role of BI in maintaining the stability of bank liquidity which is realized by reducing the reserve requirement and increasing the PLM.